Embedded Ag quantum dots into interconnected Co3O4 nanosheets grown on 3D graphene networks for high stable and flexible supercapacitors. (10th January 2017) - Wang, Junya; Dou, Wei; Zhang, Xuetao; Han, Weihua; Mu, Xuemei; Zhang, Yue; Zhao, Xiaohua; Chen, Youxin; Yang, Zhiwei; Su, Qing; Xie, Erqing; Lan, Wei; et al.
Abstract: High stable, flexible and interconnected Co3 O4 nanosheets with embedded Ag quantum dots (AgQDs) were uniformly grown on three dimensional graphene (3DG) networks and served as supercapacitor electrode to enhance the pseudocapacitance performance. The AgQDs were used to facilitate the growth of the Co3 O4 nanosheets and improve the electrical conductivity of the hybrid electrode by forming a good ohmic contact and provide direct and stable pathways for rapid electron transport. The AgQDs contribute to produce an improved areal capacitance of 421 mF cm −2 (1052.5 F g −1 ) and 53.3 mF cm −2 for the Ag/Co3 O4 /3DG hybrid, for both the three- and the two-electrode configuration, respectively. These values are about three times higher compared to a pristine Co3 O4 /3DG electrode. The capacitance retention of ∼120% after 10 4 cycles shows that a Ag/Co3 O4 /3DG hybrid can provide a long and stable cycle performance with a high specific capacitance. This study provides an effective strategy to improve the performance of electrode materials for supercapacitors with a high efficiency and long life, which makes them promising candidates for future energy-storage applications.